Fostering Competition Law and Policy: A Facade of Taiwan's Political Economy - Lawrence S. Liu (Washington University Global Studies Law Review, 2002)
The first section of this Article briefly examines how China has promoted its industrial policies since adopting its policy of reform and opening up of trade to the world outside its borders. The second section considers how these policies have promoted or restricted competition. Finally, the third section presents the author’s conclusions and opinions.
Keywords: Taiwan; ILI policy; Monopolies; Monpoly control